OPTIMALISASI PERAN APOTEKER DALAM PENCEGAHAN DIARE MELALUI EDUKASI INTERAKTIF PADA REMAJA DI PESANTREN - Onny Ziasti Fricillia; Rayhan Nurfarizki Achja; M Ridho Syahreza; Muhammad Rizky Aulia Rachman (Universitas Muhammadiyah Mataram, 2026)
Abstrak: Diare merupakan suatu penyakit yang membuat penderitanya sering buang air besar, dengan kondisi tinja yang encer. Penyakit ini bisa menyebar melalui empat hal, yaitu makanan, tinja, minuman, dan tangan. Tujuan dari kegiatan edukasi ini adalah untuk meningkatkan pemahaman santri tentang pencegahan diare melalui penyampaian ceramah, demonstrasi dan games interaktif dengan memanfaatkan media powerpoint, leaflet dan mix and match card untuk meningkatkan pemahaman para santri. Metode yang digunakan adalah sosialisasi terhadap para santri dengan menggunakan leaflet dan power point. Penilaian tingkat pemahaman antar santri dilakukan dengan menggunakan kuisoner pre-test dan post-test yang diberikan kepada 14 santri. Kuisoner yang digunakan berisi 10 pertanyaan. quasi eksperimental dengan desain satu kelompok pre-test dan post-test. Hasil yang didapatkan yaitu, terjadi peningkatan pemahaman yang dapat dibuktikan dengan melihat hasil persentase pada pre-test dan post-test dengan peningkatan dari 48,6% menjadi 84,3%. Selain itu, santri terlihat interaktif dan antusias terhadap pemaparan materi, mempraktekkan cara mencuci tangan dengan baik dan benar serta mix and match card.Abstract: Diarrhea is a disease that causes sufferers to have frequent bowel movements, with loose stools. This disease can be spread through four things: food, feces, drinks, and hands. The purpose of this educational activity is to improve students' understanding of diarrhea prevention through lectures, demonstrations, and interactive games using PowerPoint media, leaflets, and mix and match cards to improve students' understanding. The method used is socialization to students using leaflets and PowerPoint. Assessment of the level of understanding among students was carried out using a pre-test and post-test questionnaire given to 14 students. The questionnaire used contained 10 questions. The results obtained were an increase in understanding as evidenced by looking at the percentage results in the pre-test and post-test with an increase from 48.6% to 84.3%. In addition, students appeared interactive and enthusiastic about the presentation of the material, practicing how to wash hands properly and correctly, and mix and match cards.Diarrhea is a disease that causes sufferers to have frequent bowel movements, with loose stools. This disease can be spread through four things: food, feces, drinks, and hands. The purpose of this educational activity is to improve students' understanding of diarrhea prevention through lectures, demonstrations, and interactive games using PowerPoint media, leaflets, and mix and match cards to improve students' understanding. The method used is a quasi-experimental design with a single group pre-test and post-test. The results obtained are an increase in understanding as evidenced by the percentage results in the pre-test and post-test with an increase from 48.6% to 84.3%. In addition, students appeared interactive and enthusiastic about the presentation of the material, practicing how to wash hands properly and correctly, and mix and match cards.